Resilience of subarctic Scots pine and Norway spruce forests to extreme weather events - Matkala, Laura; Kulmala, Liisa; Kolari, Pasi; Aurela, Mika; Bäck, Jaana (Agricultural and Forest Meteorology, 2021)
We studied the occurrence of extreme weather events and their effects on the carbon dioxide and water exchange of two subarctic forest stands. One study site was a Scots pine site in eastern Finnish Lapland (VarriO), and the other was a Norway spruce site in western Finnish Lapland (Kenttarova). We compared short-term meteorological data with long-term data and found that the pine forest had experienced extremely warm, wet and dry years as well as cold spells during the growing season in the studied period of 2012-2018. The spruce forest was studied during the period 2003-2013, during which time it experienced extremely warm and wet summers, and dry periods, although the dry times were not statistically defined as such. The spruce forest was less resilient to warm and dry periods, as its total ecosystem respiration and respiration potential decreased during warm and dry summers, while the same effect was not seen in the pine forest. The decreased respiration values may have occurred due to slowed decomposition of organic matter. The pine forest experienced two cold spells during the studied period. One of these cold periods was more of a continuation of the previous cold spring and late start of the growing season in 2017, while the other one occurred after a warm period in 2014. The ecosystem respiration rates and gross primary production in 2017 remained low for the whole July-August time period likely due to cold-inhibited growth of ground vegetation, while in 2014 no such effect could be seen. We saw no effect of extreme weather events in the water exchange related measurements in either of the forests. Overall, both forests, especially the trees, were resilient to the weather extremes and experienced no long-term damage. Peer reviewed